The Impact of Immunosuppression and Autoimmune Disease on Severe Outcomes in Patients Hospitalized with COVID-19 - Monreal, Enric (J Clin Immunol, 2020)
Immunosuppression (IS) and autoimmune disease (AD) are prevalent in patients with severe coronavirus disease 2019 (COVID-19), but their impact on its clinical course is unknown. We investigated relationships between IS, AD, and outcomes in patients hospitalized with COVID-19. Data on consecutive admissions for COVID-19 were extracted retrospectively from medical records. Patients were assigned to one of four cohorts, according to whether or not they had an AD (AD and NAD) or were immunosuppressed (IS and NIS). The primary endpoint was development of severe acute respiratory distress syndrome (ARDS); secondary endpoints included death, and a composite of mechanical ventilation (MV) or death. A total of 789 patients were included: 569 (72.1%) male, 76 (9.6%) with an AD, and 63 (8.0%) with IS. Relative to the NIS-NAD cohort, patients in the IS-AD cohort had a significantly reduced risk of severe ARDS (adjusted hazard ratio [aHR] 0.42; 95% confidence interval [CI] 0.23–0.80; p = 0.008). No significant relationships between IS or AD status and either death or the composite of MV and death were identified, although a trend towards higher mortality was identified in the IS-NAD cohort (aHR vs NIS-NAD 1.71; 95% CI 0.94–3.12; p = 0.081). Patients in this cohort also had higher median serum levels of interleukin-6 compared with IS-AD patients (98.2 vs 21.6 pg/mL; p = 0.0328) and NIS-NAD patients (29.1 pg/mL; p = 0.0057). In conclusion, among patients hospitalized with COVID-19, those receiving immunosuppressive treatment for an AD may have a reduced risk of developing severe ARDS. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s10875-020-00927-y.